Contribution of Professional Cleaning to Indoor Air and Sewage Pollution - Marion Martienssen; Ramona Riedel; Tom Kühne (Sustainable Chemistry)
In this study, several professional cleaning products were analyzed for their impact on local air and sewage contamination. The products were first analyzed for their content of potentially harmful ingredients, their biodegradability, and the potential for the mobilization of hazardous substances from the floorings that were cleaned. The contribution of the cleaning products to sewage pollution with environmentally hazardous substances was studied at full scale. All commercially available cleaning products studied were declared to be environmentally friendly (labeled with the EU Ecolabel). However, despite being labeled as “green” products, between 16 and 24 volatile harmful ingredients were identified. An optimized experimental product, produced completely from natural raw materials, also contained several harmful substances originating from the herbal raw materials themselves. During the field study, we identified a range of trace substances in the sewage. Eight of these substances (e.g., p-cymene, butanone, eucalyptol) significantly originated from the cleaning products. Several others may have originated from the cleaning products, but other sources were also possible. The flooring materials that were cleaned contained several harmful substances themselves. The release of some substances (e.g., toluene) into the sewage significantly increased during the cleaning process.